Solid Stems and Beyond: Challenges and Future Directions of Resistance to Wheat Stem Sawfly (Hymenoptera: Cephidae). Issue 1 (12th December 2022) - Peirce, Erika S; Cockrell, Darren M; Mason, Esten; Haley, Scott; Peairs, Frank; Nachappa, Punya
Abstract: In North America, the wheat stem sawfly ( Cephus cinctus Norton) (WSS) is considered a key pest of wheat, causing significant damage to spring and winter wheat. Yield losses from WSS can be due to stem boring and/or stem cutting which causes plants to lodge. Cultural, chemical, and biological management strategies have not effectively controlled WSS. When available, host plant resistance (HPR) is an effective and environmentally friendly approach for pest management and is particularly important for controlling WSS. Solid stem genotypes are often considered the main WSS management option for producers. This review will highlight recent progress and future challenges for understanding HPR to WSS. In bread and durum wheat, we will highlight (1) the solid stem trait, (2) interactive effects of solid stem and biological control, (3) nonpreference trait, (4) novel sources of HPR, and (5) the molecular aspects of wheat–wheat stem sawfly interactions. We also highlight the available information on HPR in non-wheat crops. Future research should characterize other resistance traits that can complement solid stem genotypes to create more robust and predictable genotypes.